Làm phép nhân, áp dụng 3 hàng đẳng thức đầu tiên:
a) (x-3) (x+3) (x+2) - (x-1) (x2-3) - 5x (x+4)2 - (x-5)2
b) 2x (x-4) 2 - (x+5) (x-2) (x+2) +2 (x+5)2 - (x-1)2
c) (x+5)2 - 4x (2x+3)2 - (2x-1) (x+3) (x-3)
d) -2x (3x+2) (3x-2) +5 (x+2)2 - (x-1) (2x+1) (2x-1)
a) ( x - 3 )( x + 3 )( x + 2 ) - ( x - 1 )( x2 - 3 ) - 5x( x + 4 )2 - ( x - 5 )2
= ( x2 - 32 )( x + 2 ) - ( x3 - x2 - 3x + 3 ) - 5x( x2 + 8x + 16 ) - ( x2 - 10x + 25 )
= x3 + 2x2 - 9x - 18 - x3 + x2 + 3x - 3 - 5x3 - 40x2 - 80x - x2 + 10x - 25
= ( x3 - x3 - 5x3 ) + ( 2x2 + x2 - 40x2 - x2 ) + ( -9x + 3x + 10x - 80x ) + ( -18 - 3 - 25 )
= -5x3 - 38x2 - 76x - 46
b) 2x( x - 4 )2 - ( x + 5 )( x - 2 )( x + 2 ) + 2( x + 5 )2 - ( x - 1 )2
= 2x( x2 - 8x + 16 ) - ( x + 5 )( x2 - 4 ) + 2( x2 + 10x + 25 ) - ( x2 - 2x + 1 )
= 2x3 - 16x2 + 32x - ( x3 + 5x2 - 4x - 20 ) + 2x2 + 20x + 50 - x2 + 2x - 1
= 2x3 - 16x2 + 32x - x3 - 5x2 + 4x + 20 + 2x2 + 20x + 50 - x2 + 2x - 1
= ( 2x3 - x3 ) + ( -16x2 - 5x2 + 2x2 - x2 ) + ( 32x + 4x + 20x + 2x ) + ( 20 + 50 - 1 )
= x3 - 20x2 + 58x + 69
c) ( x + 5 )2 - 4x( 2x + 3 )2 - ( 2x - 1 )( x + 3 )( x - 3 )
= x2 + 10x + 25 - 4x( 4x2 + 12x + 9 ) - ( 2x - 1 )( x2 - 9 )
= x2 + 10x + 25 - 16x3 - 48x2 - 36x - ( 2x3 - x2 - 18x + 9 )
= x2 + 10x + 25 - 16x3 - 48x2 - 36x - 2x3 + x2 + 18x - 9
= ( -16x3 - 2x3 ) + ( x2 - 48x2 + x2 ) + ( 10x - 36x + 18x ) + ( 25 - 9 )
= -18x3 - 46x2 - 8x + 16
d) -2x( 3x + 2 )( 3x - 2 ) + 5( x + 2 )2 - ( x - 1 )( 2x + 1 )( 2x - 1 )
= -2x( 9x2 - 4 ) + 5( x2 + 4x + 4 ) - ( x - 1 )( 4x2 - 1 )
= -18x3 + 8x + 5x2 + 20x + 20 - ( 4x3 - 4x2 - x + 1 )
= -18x3 + 8x + 5x2 + 20x + 20 - 4x3 + 4x2 + x - 1
= ( -18x3 - 4x3 ) + ( 5x2 + 4x2 ) + ( 8x + 20x + x ) + ( 20 - 1 )
= -22x3 + 9x2 + 29x + 19